2015
DOI: 10.5897/ajar2014.9090
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of annual yield and quality of Valncia orange related to monthly water deficiencies

Abstract: The State of São Paulo, Brazil is the major orange producer in the world. The "Valência" orange is one of the most important cultivars for industry with a high efficiency of processed juice. Climate is the main factor of influence for citrus yield and quality and its study is fundamental for understanding the climatic requirements of the crop. The estimation of yield and quality by agrometeorological models helps to understand the effects of climate on crop cycle, besides being an option for orchards planning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…Air temperature and water deficit were the most important variables at bud formation, onset of flowering and vegetative dormancy for orchards 6-10 years of age. Moreto et al (2015) reported similar results with estimation models using multiple linear regressions as functions only of water deficit. Water restrictions during the developmental (pre-production) year had a large effect on the yield of Valência oranges, but deficits at maturity (production year) strongly affected the quality of the fruit.…”
Section: Introductionsupporting
confidence: 62%
“…Air temperature and water deficit were the most important variables at bud formation, onset of flowering and vegetative dormancy for orchards 6-10 years of age. Moreto et al (2015) reported similar results with estimation models using multiple linear regressions as functions only of water deficit. Water restrictions during the developmental (pre-production) year had a large effect on the yield of Valência oranges, but deficits at maturity (production year) strongly affected the quality of the fruit.…”
Section: Introductionsupporting
confidence: 62%
“…Moreto & Rolim (2015) an accuracy of 0.30 (Figure 4 E). ESP had the largest deviations in the estimates of the coffee supply, due to the effect of climatic factors not used in the calibration of the models, e.g., low minimum air temperature, cold winds, and frost.…”
Section: Resultsmentioning
confidence: 92%
“…These were the models that could forecast brown-eye spot in coffee plants. 67,68 Figures 7 and 8 show the graphs of brown-eye spot…”
Section: Resultsmentioning
confidence: 99%